MANFAAT PERMAINAN TRADISIONAL BOLA BEKELTERHADAP PERKEMBANGAN ANAK USIA DINI - Yeni Rahman Al Ningsih (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
Traditional games are games that benefits an can stimulate childern’s development, especially the traditional game of bekel ball. But in the PAUD instution, one of them in Al Barkah kindergarten does not apply traditional games as a medium of learning or media to stimulatee childern’s development. The research objective was to determine the benefits of this study, namely to increase the knowledge of the benefits of the traditional game bekel ball. Thre sample of this study were childern aged 5 to 6 years or group b in kindergarten Al-Barkah and the participan of this study were teacher and principals of Al-Barkah kindergarten. This research uses a qualitative approach with descriptive methods. The result of this study indicate that the traditional game bekel ball has benefit and can stimulate childern’s development.